Cardiovascular Remodeling Experienced by Real-World, Unsupervised, Young Novice Marathon Runners - D’Silva, Andrew; Bhuva, Anish N.; van Zalen, Jet; Bastiaenen, Rachel; Abdel-Gadir, Amna; Jones, Siana; Nadarajan, Niromila; Menacho Medina, Katia D.; Ye, Yang; Augusto, Joao; Treibel, Thomas A.; Rosmini, Stefania; et al. (Frontiers in Physiology, 2020)
Aims Marathon running is a popular ambition in modern societies inclusive of non-athletes. Previous studies have highlighted concerning transient myocardial dysfunction and biomarker release immediately after the race. Whether this method of increasing physical activity is beneficial or harmful remains a matter of debate. We examine in detail the cardiovascular remodelling response following competition in a first marathon. Methods Sixty-eight novice marathon runners aged 30 ±3 years were investigated 6 months before and 2 weeks after the 2016 London Marathon race in a prospective observational study. Evaluation included electrocardiography, cardiopulmonary exercise testing, echocardiography and cardiovascular magnetic resonance imaging. Results After 17 weeks unsupervised marathon training, runners revealed a symmetrical, eccentric remodelling response with 3-5% increases in left and right ventricular cavity sizes, respectively. Blood pressure fell by 4/2 mmHg with reduction in arterial stiffness, despite only 11% demonstrating a clinically meaningful improvement in peak oxygen consumption. Conclusion In the absence of supervised training, exercise-induced cardiovascular remodelling in real-world novice marathon runners is more modest than previously described and occurs even without improvement in cardiorespiratory fitness. The responses are similar in men and women, who experience a beneficial blood pressure reduction and no evidence of myocardial fibrosis or persistent oedema, when achieving average finishing times.